Dialektyka "swój"-"obcy" w prawicowej filozofii politycznej (1789-1945). Część II - Wielomski, Adam (Wydawnictwo Uniwersytetu Wrocławskiego, 2019)
The aim of the author of this text is to polemicize with the stereotype according to which nationalism is a synonym of the “extreme right.” For this purpose the method of historical exemplification was used. In Part II we discuss examples of nationalisms in various European states between the years 1890 and 1945: France, Germany, Spain, Portugal and Italy. This is the epoch when nationalism denies its initial close relationship with the political and revolutionary left. Now it is in close relations with the right. During the Boulanger and Dreyfus affaires in France, the nationalists are on the political right. Their ideology is not only right-wing but also anti-Semitic. Sometimes openly racist (Maurice Barrès). In general, however, French and Italian nationalists preach “state nationalism,” similar to the classic doctrine of raison d’état. In Spain and Portugal the right is strictly Catholic. This is the imperial right. We have here the dream of restoration of the Spanish Siglo de Oro. This project is antithetic to nationalism because it is universalist and supranational. It is different in Germany, where at the turn of the 19th and 20th centuries the whole right is lit up by the vision of conquests, German empire, struggle of races. First, the Protestant, then also the German Catholic right is chauvinistic, racist and anti-Semitic. The article ends with reflections upon the relations between political right and the idea of nationalism.
Keywords: nacjonalizm; szowinizm; rasizm; prawe skrzydło; lewe skrzydło